A near-infrared fluorescence probe with a large Stokes shift for detecting carbon monoxide in living cells and mice. (September 2020) - Liu, Yang; Wang, Wen-Xin; Tian, Yang; Tan, Min; Du, Yan; Jie, Jia; Li, Chun-Yan
Abstract: Carbon monoxide (CO) can be endogenously produced in mammalian cells and regarded as an essential cell signaling molecule in the body. And it is closely related with a range of physiological and pathological processes. Although some fluorescence probes for tracking CO are reported, near-infrared (NIR) fluorescence probe for CO with a large Stokes shift remains scarce. Herein, a NIR fluorescence probe named DCX-CO is designed and synthesized. In the probe, the allyl formate group is chosen as recognizing moiety and benzopyranonitrile-xanthene-based dye is selected as fluorophore. Upon the addition of CO, the probe shows NIR emission at 762 nm with a large Stokes shift (164 nm). Moreover, the probe displays high sensitivity for CO with 16-fold fluorescence enhancement and excellent selectivity to CO over other potential interference in biological sample. Based on the low cytotoxicity, the probe can be used for the detection of exogenous and endogenous CO in HepG2 cells and HCT116 cells. In addition, taking advantage of NIR emission with a large Stokes shift, DCX-CO is applied for monitoring CO in vivo. Graphical abstract: Image 1 Highlights: A fluorescence probe named DCX-CO is designed and synthesized for detecting CO. DCX-CO has near-infrared emission (762 nm) and large stokes shift (164 nm). The probe displays high sensitivity and selectivity toward CO. DCX-CO has been used in imaging exogenous and endogenous CO in two kinds of cells. Taking advantage of NIR emission, the probe is applied for monitoring CO in vivo.